Computational Studies on T2Rs Agonist-Based Anti–COVID-19 Drug Design - Dhanaraj, Premnath; Muthiah, Indiraleka; Rozbu, Mahtabin Rodela; Nuzhat, Samiha; Paulraj, Mosae Selvakumar (Frontiers in Molecular Biosciences, 2021)
The expeditious and world pandemic viral disease of new corona virus (SARS-coV-2) has formed a prompt urgency to discover auspicious target based ligand for the treatment of COVID-19. Symptoms of novel corona virus disease (COVID-19) typically include a dry cough, fever and shortness of breath. Recent studies on many COVID-19 patients in Italy and the UK found increasing anosmia and ageusia among the COVID-19 infected patients. SARS-CoV-2 possibly infects neurons in the nasal passage and disrupts the senses of smell and taste, like other coronaviruses, such as SARS-CoV and MERS-CoV that could target the central nervous system. Developing a drug based on the T2Rs might be of better understanding and worth finding better molecules to act against Covid-19. In this research, we have taken a taste receptor agonist molecule to find a better core molecule that may act as the best resource to design a drug or corresponding derivatives. Based on the computational docking studies, the antibiotic Tobramycin showed the best interaction against 6LU7 COVID-19 main protease. Aromatic carbonyl functional groups of the molecule established intermolecular hydrogen bonding interaction with GLN189 amino acid and it showed the two strongest carbonyl interactions with receptor protein resulting in a glide score of -11.159. To conclude, depending on the molecular recognition of the GPCR proteins, the agonist molecule can be recognized to represent the cell secondary mechanism; thus it provides enough confidence to design a suitable molecule based on the Tobramycin drug.